Resposta :
Resposta:
Explicação passo-a-passo:
temos:
a1 = 23
r = -6
an = -13
Cálculo da posição:
an = a1 + (n - 1).r
-13 = 23 + (n - 1).(-6)
-13 = 23 + (-6n + 6)
-13 = 23 - 6n + 6
-13 - 23 - 6 = -6n
-42 = -6n => multiplicando por -1, temos:
42 = 6n
n = 42/6
n = 7
Logo, o elemento -13 ocupa a 7ª posição
[tex]\sf a_n=a_1+(n-1)r[/tex]
[tex]\sf -13=23+(n-1)\cdot(-6) [/tex]
[tex]\sf -13=23-6n+6 [/tex]
[tex]\sf6n=23+6+13 [/tex]
[tex]\sf 6n=36+6 [/tex]
[tex]\sf 6n=42 [/tex]
[tex]\sf n=\dfrac{42}{6} [/tex]
[tex]\sf n=7 [/tex]
O número -13 ocupa a 7ª posição.